Bystander Intervention Opportunities and Prosocial Behaviors Among Gender and Sexual Minority College Students - Hoxmeier, Jill C. (Journal of interpersonal violence, 2022)
Bystander intervention education has proliferated as a popular strategy to address campus interpersonal violence, including intimate partner and sexual violence, which remain major public health concerns. Much of the work on bystander engagement, however, is cis- and heteronormative (i.e., centered on those individuals whose gender identity aligns with their biological sex at birth and/or who identify as heterosexual), thus failing to capture the experiences of students who identify as gender or sexual minorities (GSM), a population at increased risk for interpersonal violence. Research has demonstrated that cisgender females face an increased likelihood of victimization, which is related to greater awareness of intimate partner and sexual violence and results in more prosocial intentions and prosocial behaviors. The question remains whether this extends beyond cisgender females. The current study is a secondary analysis of data collected in a web-based sexual assault prevention course designed for undergraduate students and implemented at their respective institutions. Data from 474,395 undergraduate students, aged 18?23 years, were used to answer the research question. Results indicate that students? bystander intervention opportunities and prosocial behaviors differ based on GSM status. For example, although cisgender bisexual women, transwomen, and genderqueer/gender nonconforming (GNC) students were more likely to report having the opportunity to intervene in sexual assault situations, relative to cisgender heterosexual women, the latter two groups were less likely to intervene. Further, cisgender gay and bisexual men, as well as transmen and genderqueer/GNC students were more likely to report having the opportunity to intervene in dating abuse situations, relative to cisgender heterosexual men, and cisgender gay men were more likely to report having intervened. Given the call for centering research on minoritized student experiences, this research is a vital step toward recognizing the diversity of those experiences for GSM students, a population at risk for victimization.